تأثير استخدام التلقيح الاصطناعي على نسبة الإخصاب في بيض التفريخ عند الدجاج السوري المحلي. - جبور زهير; شعبان ميسون (Latakia University Journal -Biological Sciences Series, 2016)
This research was conducted to apply the technique of Artificial Insemination in poultry for the first time in the Syrian Arab Republic , and study the differences between the impact of the use of fresh or stored semen on the fertilization rate in hatching eggs . Results showed that the response to massage was different between cocks, It was greater in the cock A and cock B while the cock C was the least response to massage. The greater volume of ejaculate was obtained from the cock A( 0.072) ml ,and the least volume of ejaculate was obtained from the cock B (0.05) ml . The volume of ejaculate obtained from the three cocks was ranged between (0.049 -0.072) ml. The value of X in the count ranged between (230 - 237) sperm, semen concentration ranged between (4.6 - 4.7) billion sperm / ml. It also found that Insemination with a fresh semen injection yielded fertilization rate (91%), While insemination with semen injection cooling at the heat +4 ̊ C for 48 hours yielded fertilization rate (67%) . أجري هذا البحث لتطبيق تقانة التلقيح الصناعي في الدواجن لأول مرة في القطر العربي السوري، ودراسة الفروق بين تأثير استخدام السائل المنوي الطازج، أو المبرد على نسبة الإخصاب في بيض التفريخ . أظهرت النتائج أن الاستجابة للتدليك مختلفة بين الديوك، فكانت أكبر لدى الديك A، والديك B، بينما الديك C كان الأقل استجابة للتدليك , وأكبر قيمة لحجم القذفة تم الحصول عليها من الديك A 0.072 )) مل، وأقلها لدى الديك B (0.05) مل؛ إذْ تراوح حجم القذفة عند الديوك الثلاثة بين 0.049) -0.072 ) مل . تراوحت قيمة X في العد بين 230) – 237) نطفة , وتراوح تركيز السائل المنوي للديوك بين 4.6) - 4.7 ) مليار نطفة / مل . كما وجد أن تلقيح الدجاجات بالسائل المنوي الطازج أعطى نسبة إخصاب بلغت قيمتها ( 91%)، بينما كانت قيم الإخصاب الناتجة عن تلقيح الدجاجات بالسائل المنوي المحفوظ بالتبريد عند الحرارة +4̊ م لمدة 48 ساعة (67 %) .